DDoS attack detection method based on improved convolutional long short-term memory and three-way decision in SDN. - Haizhen Wang; Xiaojing Yang; Na Jia (PLoS ONE)
Software Defined Networking (SDN) is an emerging network architecture and management method, whose core idea is to separate the network control plane from the data transmission plane. It is precisely because of this characteristic that SDN controllers are susceptible to external malicious attacks, the most common of which are Distributed Denial of Service (DDoS) attacks. This paper suggests a way to find DDoS attacks called ConvLTSM-MHA-TWD. It is based on the Convolutional Long Short-Term Memory Network (ConvLSTM) and three-way decision (TWD). It solves the problem of insufficient feature extraction in SDN environment and improves classification accuracy. This method uses ConvLSTM to extract data features, and uses multi-head attention (MHA) mechanism to learn the long-distance dependence relationship in the input data, and then constructs multi-granularity feature space. ConvLSTM and MHA outputs are added to form a residual connection to further enhance feature extraction and timing modeling capabilities and solve the problem of gradient disappearance during model training. Then the three-way decision theory is used to make decisions on network behaviors immediately. For the network behaviors that cannot be made immediately, the delayed decision is made, and the feature extraction and decision are made on this part of the network behaviors again. Finally, the classification results are output. This paper conducted experiments on data sets CICIDS2017 and DDoS SDN, with accuracy rates of 0.994 and 0.977, respectively, which has better overall performance, and is suitable for training large amounts of data.